Papeis e desempenho ocupacional de mães de crianças com deficiências - Polezi, Suelen Cristina (Universidade Federal de São Carlos, 2021)
The birth of a child with a disability represents an impact on the family structure. Studies, specifically with mothers of children with disabilities, demonstrate that there is a break in the idealization of the expected child, followed by feelings such as frustration and fear, and a rupture in daily life and in the way of realizing occupational life. The aim of the present study was to investigate changes in the roles and occupational performance of mothers after the birth of their disabled child. This is a cross-sectional descriptive study with a qualitative approach conducted with 05 mothers of children diagnosed by disabilities aged between 03 and 14 years old. For data collection, the Occupational Roles List, the Canadian Occupational Performance Measure (COPM) and a semi-structured interview scrip were applied. The collected data were discussed based on the human occupation paradigm and from the perspective of the Canadian Model of Occupational Performance and Engagement. As a result, it was identified that mothers, shortly after the birth of their child, has changes in their occupational roles as workers, students, hobbies, religious and friends. However, at the present days, mothers started to play the role of volunteers with other mothers who also had children with disability. In relation to occupational performance, considering the birth of a child with a disability, mothers who currently have children aged 3 years old and dependence to perform daily life activities showed impairment in carrying out self-care, leisure and productive occupations, such as paid work, studies, aesthetic care, socializing with friends and religion. On the other hand, mothers whose children were between 6 and 14 years old who had paid work did not report problems in occupational performance, referring to achieving self-care, leisure and productivity. The mothers who reported receiving support and social support from family members, as well as from their own mothers and spouses, were the same ones who did not indicate having problems in occupational performance. It is included, then, that the experience of caring for a child with disability initially impacted the mother’s roles and occupational performance, but mothers who had social support and adapted support, returned playing roles and occupations that were previously abandoned and managed to still have positive learnings.
Roles and occupational performance of mothers of children with disabilities
Keywords: Filhos com deficiências; Mães; Papeis ocupacionais; Análise e desempenho de tarefas; Children with disabilities; Mothers; Occupational roles; Task performance and analysis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL